Simulation analysis of mixing in passive microchannel with fractal obstacles based on Murray's law. Issue 15 (18th November 2021) - Chen, Xueye; Zhang, Yaolong; Wang, Jinyuan
Abstract: In this paper, we designed fractal obstacles according to Murray's law and set them in a microchannel. We study the influence of the numbers of fractal obstacles, channel widths, branch widths, and the distance between fractal obstacles on mixing efficiency. The optimized micromixer has a high mixing efficiency of more than 90% at all velocities. This paper focuses on the analysis of the variation of mixing efficiency and pressure drop in the range of Reynolds number (Re) 0.1–150. The simulation results show that when the fluid velocity is low, the mixing efficiency of the fluids is mainly improved by molecular diffusion, when the fluid velocity is high, the microchannel with fractal obstacles can promote chaotic convection of the fluids and improve the mixing efficiency. The fractal structure based on Murray's law can be widely used in the design of passive micromixer.